2008
DOI: 10.3354/meps07302
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected patterns of facilitatory grazing revealed by quantitative imaging

Abstract: Micro-algae (the principal food of intertidal gastropods) were quantified in areas surrounding mid-shore refuges of the intertidal snail Nerita atramentosa to test the hypothesis that removal of important grazers would lead to more micro-algae. Digital colour-infrared imagery provided independent quantitative measurements of amounts of chlorophyll (as an index of amounts of micro-algae) over small areas through time. To determine the effect of grazing on micro-algal abundance, cages were used to exclude animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…There was more small-scale patchiness of micro-algae on concrete than on sandstone, possibly due to the substratum, or to differences in the ways the species grazed on the different surfaces. Little is known about the complex causes of small-scale patchiness of abundances of micro-algae on intertidal rocky shores, although grazing by different species can cause differences in amounts (Underwood & Murphy 2008) and types ) of micro-flora present. Variations in abundances and types of micro-algae due to grazing are at spatial scales of mm to cm and have not been detectable until the development of methods over recent years to measure micro-algae in situ at the relevant small scales.…”
Section: Discussionmentioning
confidence: 99%
“…There was more small-scale patchiness of micro-algae on concrete than on sandstone, possibly due to the substratum, or to differences in the ways the species grazed on the different surfaces. Little is known about the complex causes of small-scale patchiness of abundances of micro-algae on intertidal rocky shores, although grazing by different species can cause differences in amounts (Underwood & Murphy 2008) and types ) of micro-flora present. Variations in abundances and types of micro-algae due to grazing are at spatial scales of mm to cm and have not been detectable until the development of methods over recent years to measure micro-algae in situ at the relevant small scales.…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed techniques using digital colour-infrared (CIR) imaging for non-destructive quantitative measurements of algae have improved such investigations , Underwood & Murphy 2008. Field spectrometry can also quantify amounts of different pigments in biofilms in situ, providing information on the composition of the algal assemblage (Murphy et al 2005a).…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…These studies suggested that plates covered with SWT could be a useful way to manipulate temperature at a single intertidal height on rocky shores and to test for effects on early life history processes. Such an experimental manipulation would also benefit from recently developed infrared imaging techniques used to quantify fine-scale variation in both physical and biological characteristics of rocky intertidal shores (Murphy et al 2006, Underwood & Murphy 2008, Chapperon & Seuront 2011, Cox & Smith 2011. The advantage of such infrared sensing is that temperature variability can be assessed at spatial scales relevant to newly settled benthic marine invertebrates.…”
Section: Introductionmentioning
confidence: 99%